2022
DOI: 10.3390/jcm11020447
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Peripheral Monocytes with IL-1β in the Pathogenesis of West Syndrome

Abstract: Neuroinflammation has been implicated in the pathogenesis of West syndrome (WS). Inflammatory cytokines, including interleukin-1β(IL-1β), have been reported to be associated with epilepsy. However, the assessment of cytokine changes in humans is not always simple or deterministic. This study aimed to elucidate the immunological mechanism of WS. We examined the intracellular cytokine profiles of peripheral blood cells collected from 13 patients with WS, using flow cytometry, and measured their serum cytokine le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Xu et al provided direct evidence that IL-17and GM-CSF-producing gdT cells were concentrated in epileptogenic lesions from brains of DRE patients, and their numbers were positively related to disease severity, although the numbers of Treg cells were inversely related (241). Other studies involving pediatric DRE patients suggested significant changes of intracellular IFN-g concentration among CD4 + T cell populations (242), differentiated immunological parameters caused by medication choices (243), and one study on DRE patients also confirmed higher levels of PD-1 in the serum and CSF (244).…”
Section: Epilepsymentioning
confidence: 99%
“…Xu et al provided direct evidence that IL-17and GM-CSF-producing gdT cells were concentrated in epileptogenic lesions from brains of DRE patients, and their numbers were positively related to disease severity, although the numbers of Treg cells were inversely related (241). Other studies involving pediatric DRE patients suggested significant changes of intracellular IFN-g concentration among CD4 + T cell populations (242), differentiated immunological parameters caused by medication choices (243), and one study on DRE patients also confirmed higher levels of PD-1 in the serum and CSF (244).…”
Section: Epilepsymentioning
confidence: 99%